Acute lymphoblastic leukemia in pregnancy: a case report with literature review. (October 2013) - Ticku, Jonathan; Oberoi, Shilpa; Friend, Sarah; Busowski, John; Langenstroer, Mary; Baidas, Said
The management of acute lymphoblastic leukemia (ALL) during pregnancy requires treatment with high-dose chemotherapy that can pose risks to both the mother and fetus. Special consideration to chemotherapy regimen and its doses and to fetal gestational age at the time of chemotherapy administration should be taken in order to limit fetal exposure while still providing optimal therapy to the mother. Here we describe a 22-year-old patient who was diagnosed at 26 weeks gestation with ALL and was treated in the third trimester with HyperCVAD (cytoxan, vincristine, adriamycin, dexamethasone) combination chemotherapy giving birth via Caesarean section to a healthy baby girl 4 weeks after induction chemotherapy.